Geomorphology of Pereiro Massif, Northeast Brazil - Edmundo Rodrigues de Brito; Frederico de Holanda Bastos; Vanda Carneiro de Claudino Sales; Abner Monteiro Nunes Cordeiro; Lionel Siame (Revista Brasileira de Geomorfologia)
The Pereiro Massif, located in northeastern Brazil, has a lithostructural evolution resulting from different cycles, with records related to the Brazilian (Neoproterozoic) orogenic cycles, as well as Mesozoic tectonic events and Cenozoic climatic and depositional cycles. Understanding the morphogenesis and morphostructural characterization of the Pereiro Massif involved understanding how the structural and lithological constraints present in the deformation zones of the Precambrian basement, with a preferential NE-SW direction, act in directing the denudational processes responsible for the topographic downwearing due to Cenozoic climatic variations. The analysis of structural conditions allowed the establishment of two macro geomorphological units, subdivided into 5 sub-units, considering the drainage morphometry using the Slope x Extent Index (RDE). Denudation rates, analyzed based on the production of cosmogenic nuclides (10Be) and age measurements by Optically Stimulated Luminescence (OSL) were also adopted in the analysis of the geomorphological evolution of the massif. The main results obtained suggests that the Pereiro Massif is under structural control related to Cretaceous and Cenozoic reactivations, which intensified the denudation processes in the massif, especially in its eastern part, where denudation rates are higher, leaving no clear evidence of neotectonic activity in the morphogenesis and mosphostructure of Pereiro.